(untitled) (Annals of Medical Research, 2021)
Aim: In a community based teaching hospital setting, to explore role of dual-phase parathyroid scintigraphy and surgeon experience in minimally invasive parathyroidectomy.Material and Methods: During 4-year period, from January 2013 to December 2016, 136 of 170 patients those were diagnosed with primary hyperparathyroidism were selected for this retrospective study. For detection of hyper-functioning parathyroid tissue, routine neck ultrasound and 99mTc-MIBI dual phase parathyroid scintigraphy were performed. All scintigraphy scans were evaluated by nuclear medicine physicians and surgeons together. Patients with suspected multiglandular diseases and familial cases were excluded. Enlarged glands were identified by surgeons intraoperatively. Specimens were sent for frozen section analysis.Results: Without using intraoperative parathormone monitoring or gamma probe, combination of neck ultrasound, surgeon-nuclear physician evaluated parathyroid scintigraphy scan and resection of surgeon-identified diseased gland resulted in 100% cure rate for this group of patients. Conclusion: Operative experience of surgeon and review of preoperative parathyroid scintigraphy scan had remarkable impact on outcomes. Minimally invasive parathyroidectomy can be held successfully at community-based hospitals under specific conditions without using intraoperative parathormone or gamma probe.